Management of IATF as the Main Breeding Method for Genetic Improvement at Farm Oasis, Caño Negro, Los Chiles (Biocenosis, 2022)
In Costa Rica there are many farms dedicated to cattle production with the use of different breeding techniques and breeds according to the ultimate purpose of production. The productive and genetic improvement in the Oasis farm is based on the development and work with the animals that are produced through the use of Fixed Time Artificial Insemination (FTAI) as the main pregnancy method, managing and controlling the activity by applying the use of records or data collection of livestock activity. The actions consider a sustainable management of natural resources and better management of production times; in order to obtain improvements in the medium term within the current production system. Purebred bulls have a high commercial value, therefore, for a small herd, it is difficult to opt for improvements with these animals that provide the main characteristics and meet the selection requirements. Consequently, with the tool or implementation of artificial insemination, animals with these desired conditions and characteristics were obtained at a very low cost and endorsed by different entities to improve the progeny of a bovine herd, in addition to being bulls with a high value of heritability in their offspring, with greater adaptability to adversity and with a high genealogical value.
Keywords: Fixed time artificial insemination; sustainable management; food safety; reproductive biotechnology; productive entrepreneurship